Labelling environmental and terroir attributes: Young Italian consumers' wine preferences. (1st July 2021) - Capitello, Roberta; Agnoli, Lara; Charters, Steve; Begalli, Diego
Abstract: This study advances the field of sustainability and origin-related attributes with an analysis of the role of a carbon reduction claim in consumer choice when it is labelled in conjunction with terroir cues on a bottle of wine. Data derive from a survey, including a Discrete Choice Experiment, with a sample of 982 Italian young consumers. The estimation of a Latent Class Model in willingness-to-pay space shows seven consumer segments characterized by different motivations and relationships between the environmental claim and the terroir indications. Socio-demographics and behavioural attitudes further describe demand heterogeneity. Results indicates that the carbon claim has a positive impact on the utility of three groups together comprising 46% of the sample and described as follows: those seeking original wines; price-sensitive and with low willingness-to-pay for both carbon and terroir claims; or highly interested in many different terroir expressions. The study suggests that wineries can use environmental attributes in conjunction with terroir ones following three different strategic patterns: to enhance the modernity of a wine; to connect the origin of a wine with production specificities shared among typical wine producers and; to echo product quality in the case of less reputed or cheap Protected Designation of Origin wines. This is of relevance for the wine industry as an increasing number of producers are moving toward sustainable certifications and paying more attention to the visual aspects of packaging and to new technologies for wine communications. Graphical abstract: Image 1 Highlights: Environmental and terroir attributes play an increasingly important role in wine marketing. Young people show different motivations in using environmental and terroir cues. The carbon claim has a positive impact on utility for 46% of the surveyed sample. Three major attitudes drive consumers towards sustainable wine: originality, price and terroir. Consumer preferences result in three different marketing options for wine businesses.